Molecular Regulation of Contractile Smooth Muscle Cell Phenotype: Implications for Vascular Tissue Engineering - Beamish, Jeffrey A. (Mary Ann Liebert, Inc., 2010)
The molecular regulation of smooth muscle cell (SMC) behavior is reviewed, with particular emphasis on stimuli that promote the contractile phenotype. SMCs can shift reversibly along a continuum from a quiescent, contractile phenotype to a synthetic phenotype, which is characterized by proliferation and extracellular matrix (ECM) synthesis. This phenotypic plasticity can be harnessed for tissue engineering. Cultured synthetic SMCs have been used to engineer smooth muscle tissues with organized ECM and cell populations. However, returning SMCs to a contractile phenotype remains a key challenge. This review will integrate recent work on how soluble signaling factors, ECM, mechanical stimulation, and other cells contribute to the regulation of contractile SMC phenotype. The signal transduction pathways and mechanisms of gene expression induced by these stimuli are beginning to be elucidated and provide useful information for the quantitative analysis of SMC phenotype in engineered tissues. Progress in the development of tissue-engineered scaffold systems that implement biochemical, mechanical, or novel polymer fabrication approaches to promote contractile phenotype will also be reviewed. The application of an improved molecular understanding of SMC biology will facilitate the design of more potent cell-instructive scaffold systems to regulate SMC behavior.